Residenciais fechados: loteamentos, condomínios de casas térreas ou assobradadas e condomínios de lotes - Rosa, Fernanda Christina de Souza (2019)
Restricted access residential properties are a reality in Brazilian cities, with practical, terminological and legal confusion regarding the gated developments (loteamentos fechados, or controlled access developments), the one or two-story houses condominiums and the condominiums of lots. In this work, we analyze these developments from the urban point of view, focused on the importance of urban planning by municipalities, which, supported by democratic management instruments, should promote adequate land use through planning and controlling of land use, subdivision and occupation of urban land. We go into the real estate aspects to verify their common points and divergences, and in particular to frame them legally, be it with regard to the laws applicable to each institute, or to address the controversial points that have provoked several doctrinal debates and jurisprudence since the 1970s. We analyze to what extent law no. 13,465 / 2017 contributed to reducing the controversial legal issues, as well as the aspects that should be regulated by the municipalities for the implementation of these enterprises, along with the adaptations that should be made by the real estate officers in the analysis of titles for the recordings required for their regularity